Control of Virulence Gene Expression by the Master Regulator, CfaD, in the Prototypical Enterotoxigenic Escherichia coli Strain, H10407 - Hodson, Carla; Yang, Ji; Hocking, Dianna M.; Azzopardi, Kristy; Chen, Qianyu; Holien, Jessica K.; Parker, Michael W.; Tauschek, Marija; Robins-Browne, Roy M. (Frontiers in Microbiology, 2017)
Enterotoxigenic E. coli (ETEC) is the most common bacterial cause of diarrhea in children in developing countries, as well as in travelers to these countries. To cause disease, ETEC needs to produce a series of virulence proteins including enterotoxins, colonization factors and secretion pathways, which enable this pathogen to colonize the human small intestine and deliver enterotoxins to epithelial cells. Previously, a number of studies have demonstrated that CfaD, an AraC-like transcriptional regulator, plays a key role in virulence gene expression by ETEC. In this study, we carried out a transcriptomic analysis of ETEC strain, H10407, grown under different conditions, and determined the complete set of genes that are regulated by CfaD. In this way, we identified a number of new target genes, including rnr-1, rnr-2, etpBAC, agn43, flu, traM and ETEC_3214, whose expression is strongly activated by CfaD. Using promoter-lacZ reporters, primer extension and electrophoretic mobility shift assays, we characterized the CfaD-mediated activation of several selected target promoters. We also showed that the gut-associated environmental signal, sodium bicarbonate, stimulates CfaD-mediated upregulation of its virulence target operons. Finally, we screened a commercial small molecule library and identified a compound (CH-1) that specifically inhibited the regulatory function of CfaD, and by 2-D analoging, we identified a second inhibitor (CH-2) with greater potency.